Comparison of methods for vehicle emissions calculation and their sensitivity to fleet structuring - O. V. Maksimova; V. A. Ginzburg; V. M. Lytov (Вестник СибАДИ)
Introduction. The study presents the results of the calculation of greenhouse gas emissions and polluting solids by vehicles fleet on the basis of three independent estimates of the set of initial data on the breakdown of the fleet by technological classes (the number and types of vehicles of different ecological classes, annual mileage, etc.). Such data is not provided in the forms of state statistical reports and is generated by the researchers. The article solves the problem of determining their significance for calculating the total emissions in the context of a large data array for the territory of Russia.Materials and methods. Three different versions to the calculation of greenhouse gas emissions (basic version, equalization of transport work and new approach - equalization of fuel consumption) are proposed in order to identify differences in the obtained emissions in different conditions (i.e., to determine quantitative characteristics of the accuracy of the final values). A new method has been developed for assessing the effect of average mileage and vehicle distribution on classes on the total emissions values, implemented within each proposed version. In addition, two types of sensitivity formulas are formed by the authors to assess the impact of vehicle distribution on classes and average mileage to final emission calculations. The use of these formulas provides scientific analysis and interpretation of the influence of the factors in expert review on the final values of the emissions of each type.Results. The differences in sorting cars into classes in expert evaluations were revealed and the closest ones are determined. It was found that the most sensitive to changes in mileage and class of cars, on which fuel consumption depends, are CO2 emissions.Conclusion. The scientific sensitivity analysis of both types showed the importance of maintaining the principles underlying expert evaluation from year to year in order to ensure that the results obtained are consistent.